2016
DOI: 10.2217/fmb-2016-0166
|View full text |Cite
|
Sign up to set email alerts
|

Understanding Protein Glycosylation Pathways in Bacteria

Abstract: Through advances in analytical methods to detect glycoproteins and to determine glycan structures, there have been increasing reports of protein glycosylation in bacteria. In this review, we summarize the known pathways for bacterial protein glycosylation: lipid carrier-mediated 'en bloc' glycosylation; and cytoplasmic stepwise protein glycosylation. The exploitation of bacterial protein glycosylation systems, especially the 'mix and match' of three independent but similar pathways (oligosaccharyltransferase-m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(10 citation statements)
references
References 91 publications
0
10
0
Order By: Relevance
“…Several studies have demonstrated that glycosylation is one of the most important modifications used by P. gingivalis to increase its virulence. Bacterial glycosylation is related mainly to macromolecules exposed to the external environment [65] and is important for bacterial interactions with and adhesion to the host cells [66]. Among the best-characterized glycoconjugates are gingipains [67, 68], an outer membrane OMP85 protein [69], and Mfa1 fimbriae [70].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have demonstrated that glycosylation is one of the most important modifications used by P. gingivalis to increase its virulence. Bacterial glycosylation is related mainly to macromolecules exposed to the external environment [65] and is important for bacterial interactions with and adhesion to the host cells [66]. Among the best-characterized glycoconjugates are gingipains [67, 68], an outer membrane OMP85 protein [69], and Mfa1 fimbriae [70].…”
Section: Discussionmentioning
confidence: 99%
“…1). In most wellcharacterized systems N-glycosylation occurs in the eukaryotic endoplasmic reticulum or bacterial periplasm and requires an oligosaccharyltransferase (OST) to transfer a preassembled oligosaccharide from a lipid donor to asparagine residues in substrate proteins (43)(44)(45). In contrast, NTHi employs HMW-C, a soluble cytoplasmic protein belonging to the GT41 family of glycosyltransferases, a family which is otherwise comprised of O-GlcNAc transferases (46).…”
Section: Introductionmentioning
confidence: 99%
“…For a long time, protein glycosylation was deemed to be restricted to eukaryotes. So far, it has been clearly established that bacteria, including pathogens possess both O-and N-linked glycosylation pathways that display many commonalities with their eukaryotic counterparts, as well as some unexpected variations (2,3). N-linked protein glycosylation commonly occurs at the side chain amide of an Asn residue in the sequences Asn-X-Ser/Thr of the targeted proteins, where X can be any amino acid except proline.…”
mentioning
confidence: 99%